Yield gap in cowpea plants as function of water déficits during reproductive stage - Paulo J. O. P. Souza; Vivian D. da S. Farias; João V. N. Pinto; Hildo G. G. C. Nunes; Everaldo B. de Souza; Clyde W. Fraisse (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The cowpea bean presents low productivity in the Pará state, Brazil, due to low soil fertility and climatic adversity, mainly water deficiency. The aim of this study was to evaluate the yield gap of cowpea bean in northeast of Para state in response to water deficit during its reproductive phase. The experiment was carried out in Castanhal, PA, Brazil, during 2015 and 2016. A randomized block design with six repetitions and four treatments was used; where T1 consisted of 100% replacement of the crop evapotranspiration (ETc), T2 to 50%, T3 to 25% and T4 without irrigation, in the reproductive phase. The yield was determined at R9 stage. The simulations with the SARRAZON model were carried out with different sowing dates. The total deficiencies in the reproductive phase were spatialized considering the 30 locations in order to assess the temporal and spatial seasonality of water availability and the sowing period in the study region. The cowpea bean was sensitive to soil water availability with considerable reductions in productivity due to the increase in water deficit compared to the treatment T1 (100% ETc). When water deficits reached more than 47 mm, there were yield gaps over 20%. According to the spatial variability of simulated water deficiency, the sowing of cowpea bean in regions located above 2° latitude may extend until June 20 without showing high yield gaps.